Identification of somatic gene mutations in penile squamous cell carcinoma. Issue 10 (27th July 2015) - Ferrándiz‐Pulido, Carla; Hernández‐Losa, Javier; Masferrer, Emili; Vivancos, Ana; Somoza, Rosa; Marés, Roso; Valverde, Claudia; Salvador, Carlos; Placer, Jose; Morote, Juan; Pujol, Ramon M.; Ramon, Santiago; et al.
<x xml:space="preserve">Abstract</x> There is a lack of studies on somatic gene mutations and cell signaling driving penile carcinogenesis. Our objective was to analyze somatic mutations in genes downstream of EGFR in penile squamous cell carcinomas, especially the mTOR and RAS/MAPK pathways. We retrospectively analyzed somatic mutations in 10 in situ and 65 invasive penile squamous cell carcinomas by using Sequenom's Mass Spectrometry iPlex Technology and Oncocarta v1.0 Panel. The DNA was extracted from FFPE blocks and we identified somatic missense mutations in three in situ tumors and in 19 invasive tumors, mostly in PIK3CA, KRAS, HRAS, NRAS, and PDGFA genes. Somatic mutations in the PIK3CA gene or RAS family genes were neither associated with tumor grade, stage or outcome, and were equally often identified in hrHPV positive and in hrHPV negative tumors that showed no p53 expression. Mutations in PIK3CA, KRAS, and HRAS are frequent in penile squamous cell carcinoma and likely play a role in the development of p53‐negative tumors. Although the presence of these mutations does not seem to correlate with tumoral behavior or outcome, they could be biomarkers of treatment failure with anti‐EGFR mAb in patients with penile squamous cell carcinoma. © 2015 Wiley Periodicals, Inc.